1998
DOI: 10.1267/ahc.31.211
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Connexin 26, 32 and 43 in Rat Parotid Glands.

Abstract: Double immuno-electron microscopy confirmed that connexin 26 and 32 were co-localized in the same gap junction. These results suggest that connexin 26 and 32 are associated with secretory function and permeability between endpiece cells and that connexin 43 is associated with contraction of the myoepithelial cells that surround intercalated ducts in the rat parotid glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…(1994) reported that Cx32 and Cx26 in rat salivary glands were colocalized within same GJ plaques). Lee et al . (1998) suggested that Cx26 and 32 were associated with secretary function and permeability.…”
Section: Discussionmentioning
confidence: 99%
“…(1994) reported that Cx32 and Cx26 in rat salivary glands were colocalized within same GJ plaques). Lee et al . (1998) suggested that Cx26 and 32 were associated with secretary function and permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Right: magnitude of the coupling of control (Con) and male Cx32-deficient animals was similar (10.0 Ϯ 2.5 and 10.6 Ϯ 2.5 ps, respectively) whereas that of the few cell pairs that were coupled from the Cx32-deficient female glands had a lower conductance (1.8 Ϯ 1.2 ps). *P Ͻ 0.05. via a protein kinase C system (8,9). Although it is clear that gap junctions are present and can be regulated, there are no data on either mouse or rat lacrimal or salivary gland systems to show the role of gap junctions in the secretory process itself.…”
Section: Discussionmentioning
confidence: 99%
“…12). They have not been documented in SDs either by freeze‐fracture (Shimono et al, 1980) or by immunocytochemistry (Hirono et al, 1995; Lee et al, 1998). Recently, however, Iwasa and Kondo (1999) have reported the presence of many point contacts (focal gap junctions?)…”
Section: Innervationmentioning
confidence: 99%